Early life health and adult earnings: Evidence from a large sample of siblings and twins - Petter Lundborg; Anton Nilsson; Dan-Olof Rooth (Institute for the Study of Labor (IZA), 2011)
We study the relationship between early life health and adult earnings using a unique dataset that covers almost the entire population of Swedish males born between 1950 and 1970. The health information is obtained from medical examinations during the mandatory military enlistment tests at age 18, which we have further linked to register data on adult earnings. We find that most types of major diagnoses have long-run effects on future earnings with the largest effects resulting from mental conditions. Including sibling fixed effects or twin-pair fixed effects reduces the magnitudes of the estimates, although remaining substantial.
urn:nbn:de:101:1-20110629900
Keywords: I1; J24; J31; 330; earnings; health; specific conditions; siblings; twins